Adsorption Dyes in Aqueous Solutions by Activated Carbon-Based White Wood - Elmerzouki, K.; Bimaghra, I.; Khalidi, A. (Journal of Applied Solution Chemistry and Modeling, 2016)
Among the dyes, the blue disperse and reactive orange have well recognized toxicities and dissemination facilities in the different compartments of the environment. Various regulations set maximum permissible levels of these dyes in both drinking water and industrial discharges. In order to comply with these various standards, many depollution techniques have been developed in recent years. Our choice is to carry out the adsorption of activated carbon based wood because this adsorption has main advantages of being more effective and easy to implement. Furthermore, the use of less expensive non-conventional adsorbents guarantees its economic feasibility. However, this elimination is affected by several parameters related to the carbon atom, to the solution and the active suspension. The adsorption results for Disperse Blue and orange reactive with activated charcoal showed adsorption capacity up to 4.8 mg / g and 12.4 mg / g. The study showed that the adsorption of activated carbon prepared from wood is more effective for the removal of these two wastewater dyes.